A Randomized Trial of Intrapartum Fetal ECG ST-Segment Analysis. Issue 12 (December 2015) - Belfort, Michael A.; Saade, George R.; Thom, Elizabeth; Blackwell, Sean C.; Reddy, Uma M.; Thorp, John M.; Tita, Alan T. N.; Miller, Russell S.; Peaceman, Alan M.; McKenna, David S.; Chien, Edward K. S.; Rouse, Dwight J.; et al.
Abstract : ABSTRACT: In 2005, the Food and Drug Administration approved the use of fetal electrocardiographic (ECG) ST-segment analysis (STAN) as an adjunct to conventional electronic fetal heart rate monitoring. However, evidence that such monitoring reduces the rates of neonatal encephalopathy, acidemia, and operative delivery is lacking. This study assesses the effects of using fetal ECG STAN on perinatal outcomes. For this trial, women with a singleton fetus at more than 36 weeks of gestation planning for a vaginal delivery and with cervical dilation of 2 to 7 cm were invited. A total of 11, 108 women were randomly assigned to "masked" (5576 women) or "open" (5532 women) monitoring. Masked monitoring functioned as conventional electronic fetal heart rate monitors, and monitoring in the open mode displayed additional information used for detecting and interpreting uncertain fetal heart rate patterns. In addition, those randomized to "open" had some specific algorithms related to the fetal STAN information. The primary study outcomes were intrapartum fetal death, neonatal death, an Apgar score of 3 or less at 5 minutes, neonatal seizure, an umbilical-artery blood pH of 7.05 or less with a base deficit of 12 mmol/L or more, intubation for ventilation at delivery, or neonatal encephalopathy. No significant differences in baseline characteristics were seen between the 2 groups. The primary outcome occurred in 52 neonates (0.9%) born to women in the open group and in 40 neonates (0.7%) delivered by women in the masked group (relative risk, 1.31; 95% confidence interval, 0.87–1.98; P = 0.20). With respect to the incidences of individual components of the primary outcome, the only difference between the groups was that the frequency of an Apgar score of 3 or less at 5 minutes was higher among neonates of patients in the open group than among neonates of patients in the masked group (0.3% vs 0.1%; P = 0.02). There were no significant differences between the 2 groups in the overall rates of cesarean delivery (16.9% vs 16.2%; P = 0.30) or any operative delivery (22.8% vs 22.0%; P = 0.31). This large, randomized trial showed that ST-segment analysis as an adjunct to continuous electronic fetal monitoring (EFM) neither improved neonatal outcomes nor reduced the rates of cesarean delivery or operative vaginal delivery.